Overview of Exclusive Breastfeeding Infants in Billa Cenge Health Center - Zudy, Sius Aryanto; Aspatria, Utma; Boeky, Daniela L. Adeline (Timorese Journal of Public Health, 2022)
Breast milk is the best nutrition in early life, to meet the growth and development needs of babies until adulthood. The Billa Cenge Health Center had 186 babies in 2019, there were 148 babies who did not receive exclusive breastfeeding and 38 babies who received exclusive breastfeeding. The purpose of the study was to find out the description of exclusive breastfeeding for infants 6-12 months in Billa Cenge Public Health Center, North Kodi District, Southwest Sumba Regency. The method used in this study was quantitative research. The study was conducted at the Billa Cenge Health Center in September-December 2021. The population in this study were infants aged 6-12 months, with a total sample of 186 infants. The sampling technique used in this study, namely random sampling. The results showed that respondents aged > 30 years gave the most exclusive breastfeeding (52.3%),respondents with higher education levels gave the most exclusive breastfeeding (44.6%), and respondents with low levels of knowledge gave the most. Exclusive breastfeeding (41.5%) compared to respondents who had a high level of education and respondents who had a negative attitude but gave exclusive breastfeeding (40%). It is recommended to health workers be more active in conducting counseling about exclusive breastfeeding to the community, especially to mothers who have babies, so that mothers increase their ability to determine success in exclusive breastfeeding.